2001
DOI: 10.1021/ic010250w
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bonding Cavities about Metal Ions:  Synthesis, Structure, and Physical Properties for a Series of Monomeric M−OH Complexes Derived from Water

Abstract: The tripodal ligand N[CH2CH2NHC(O)NHC(CH3)3]3 ([H61]) was used to synthesize a series of monomeric complexes with terminal hydroxo ligands. The complexes [Co(II/III)H31(OH)](2-/1-), [Fe(II/III)H31(OH)](2-/1-), and [Zn(II)H31(OH)](2-) have been isolated and characterized. The source of the hydroxo ligand in these complexes is water, which was confirmed with an isotopic labeling study for [Co(III)H31(OH)](1-). The synthesis of [M(II)H31(OH)](2-) complexes was accomplished by two routes. Method A used 3 equiv of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 41 publications
4
87
0
Order By: Relevance
“…The work by Borovik 12,18,19 is an elegant display of the importance of hydrogen bonding motifs in the preparation and characterization of iron complexes supported by the urea-based, tripodal ligand framework tris{(N′-tert-butylureayl)-N-ethylene]-amine. 23 Upon exposure to oxygen, formation of the iron-(II)/iron(III)−hydroxo species is observed, stabilized by the intramolecular hydrogen bonding framework. The work by Borovik has focused on intramolecular hydrogen bonds and intermolecular hydrogen bonds; 24 very bulky ligands 21,26b have also been used to stabilize monomeric Fe−OH complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The work by Borovik 12,18,19 is an elegant display of the importance of hydrogen bonding motifs in the preparation and characterization of iron complexes supported by the urea-based, tripodal ligand framework tris{(N′-tert-butylureayl)-N-ethylene]-amine. 23 Upon exposure to oxygen, formation of the iron-(II)/iron(III)−hydroxo species is observed, stabilized by the intramolecular hydrogen bonding framework. The work by Borovik has focused on intramolecular hydrogen bonds and intermolecular hydrogen bonds; 24 very bulky ligands 21,26b have also been used to stabilize monomeric Fe−OH complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[66,67] Masuda has also demonstrated that amide-appended tetradentate tripodal N 4 -donor ligands can be used to stabilize a variety of novel copper-and/or iron-hydroxo, -hydroperoxo, and -alkylperoxo species. [68][69][70][71][72][73] These latter complexes are particularly interesting in that each contains the {[6-(pivaloylamido)-2-pyridyl]methyl}amine structural component within the supporting chelate ligand. Further studies are clearly needed to determine how changes in the nature of the metal ion influence the amide-cleavage reactivity.…”
Section: Amide Cleavagementioning
confidence: 99%
“…It took longer to recognize that additional factors and in particular the microenvironment around a potentially ionizable group and the medium (dielectric constant of solvent) markedly contribute to the overall effect. It was the undisputed achievement of model bioinorganic chemistry, among others, to provide a deeper understanding of this phenomenon [3][4][5][6][7][8][9]. When the field of metal-nucleic acid chemistry became popular during the second half of the last century, the topic of acidity/basicity alterations of nucleobases due to metal binding likewise started to receive attention, last but not least because of its potential impact on biorelevant features such as nucleobase tautomerism, base pairing and mispairing patterns, as well as acid-base catalysis involving nucleic acids .…”
Section: Introductionmentioning
confidence: 99%